Insulin degludec 100 U/mL for treatment of spontaneous diabetes mellitus in dogs - Jocelyn Mott; Arnon Gal; Antonio Maria Tardo; Alisa Berg; Riley Claude; Alexis Hoelmer; Mei Lun Mui; Avin Arjoonsingh; Chen Gilor (Journal of Veterinary Internal Medicine)
Abstract Background The advantages of insulin degludec 100 U/mL (IDeg100) in the treatment of diabetes mellitus (DM) include consistent release, predictable glucose‐lowering effect, and minimal day‐to‐day variability. Hypothesis/Objectives To describe the use of IDeg100 in dogs with DM, level of diabetic control and adverse effects. Animals Thirty‐three client‐owned dogs with DM. Methods A prospective, multi‐institutional, uncontrolled study of newly diagnosed or previously insulin‐treated, with or without comorbidities and with or without concurrent medications. Clinical signs and continuous glucose monitoring data were monitored and guided insulin dose adjustments. A per‐protocol analysis was performed. Results The final dose of IDeg100 in dogs was 1.3 U/kg (median, range, 0.4‐2.2) achieved in 14 days (median, range, 3‐32). Seventy‐nine percent (26/33) of the dogs had comorbidities with 42% (11/26) having more than 1 comorbidity. Sixty‐four percent (21/33) of dogs were receiving concurrent medications with 62% (13/21) receiving more than 1 non‐insulin medication. Seventy‐six percent (25/33) were scored as having excellent/very good DM control. From baseline to study exit, dogs showed improvements in both ALIVE DM clinical score (from 3 [0‐8, 96.49% CI (2‐5)] to 1 [0‐7, 96.49% CI (1‐2)]; P = .0007) and average 3‐day interstitial glucose (from 332.8 ± 68.7 mg/dL, 95% CI [308.8‐357.2] to 229.0 ± 56.3 mg/dL [CI 209.0 ‐ 248.9]; P < .0001). Conclusions and Clinical Importance Insulin degludec 100 U/mL is effective for the treatment of dogs with DM. Eighty‐four percent (28/33) of dogs responded to once daily dose of IDeg100 with low frequency of clinical hypoglycemia.